2020
DOI: 10.1155/2020/6705784
|View full text |Cite
|
Sign up to set email alerts
|

Acute Fatty Liver Disease of Pregnancy in the Second Trimester

Abstract: Acute fatty liver of pregnancy (AFLP) is a rare disorder that typically presents in the third trimester. We report a case of a 21-year-old woman with a history of intrauterine fetal demise at 19 weeks’ gestation who developed fulminant liver failure 1 week after the fetal demise. She was diagnosed with AFLP as per the Swansea criteria. An orthotopic liver transplant was attempted but was unsuccessful. AFLP usually presents between the 30th to 38th weeks of gestation. However, it can occur in the postpartum per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
3
0
4
Order By: Relevance
“…A separate cohort analysis found that 19% of AFLP cases had mutations in the MTP α-subunit responsible for LCHAD deficiency [13]. Most cases of AFLP occur in the third trimester or early postpartum period, but there are case reports as early as the second trimester with the earliest reported case at 18 weeks of gestation [1][2][3][4][5][6]. Clinically, AFLP leads to liver failure but is also associated with renal failure, coagulopathy, hypoglycemia, encephalopathy, and multisystem organ failure [17][18][19]-all of which occurred in the presented case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate cohort analysis found that 19% of AFLP cases had mutations in the MTP α-subunit responsible for LCHAD deficiency [13]. Most cases of AFLP occur in the third trimester or early postpartum period, but there are case reports as early as the second trimester with the earliest reported case at 18 weeks of gestation [1][2][3][4][5][6]. Clinically, AFLP leads to liver failure but is also associated with renal failure, coagulopathy, hypoglycemia, encephalopathy, and multisystem organ failure [17][18][19]-all of which occurred in the presented case.…”
Section: Discussionmentioning
confidence: 99%
“…e pathophysiology remains unclear, but research has implicated defective mitochondrial fatty acid oxidation as a contributing factor. AFLP typically presents in the third trimester or early postpartum period, but rare cases have been described in the second trimester [1][2][3][4][5][6]. Diagnosis is usually based on the Swansea criteria [7] in conjunction with serologic and biochemical testing although liver biopsy can be performed under certain circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Her fetus was delivered at 19 weeks and 1 day of gestation. A PubMed search using the keywords "acute fatty liver of pregnancy" and "second trimester" revealed only five cases reported to date, which presented at 22, 3 23, 4 22, 5 19, 6 and 18 7 weeks' gestation with delivery at 20 weeks. 7 Therefore, to the best of our knowledge, this is the earliest AFLP diagnosis and pregnancy termination case to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Múltiples estudios han sugerido que no es esencial solicitar la biopsia hepática, únicamente en los casos en los que el diagnóstico es incierto (12,17). Para el diagnóstico de esta patología existen los criterios de Swansea, los cuales incluyen síntomas y alteraciones de laboratorios (los cuales se muestran en la tabla 1), que se utilizan únicamente a partir del tercer trimestre (4,18). Estos criterios fueron validados en un gran estudio de cohorte realizado en el Reino Unido, y cuando esta herramienta fue aplicada a un gran número de pacientes con sospecha de enfermedades hepáticas del embarazo que fueron sometidas a biopsia hepática, estos tuvieron un valor predictivo positivo de 85% y un valor predictivo negativo del 100% para esteatosis hepática microvascular.…”
Section: Clínica Y Diagnósticounclassified
“…Ciertos casos podrían tardar hasta 4 semanas para su completa resolución, y el manejo de la coagulopatía podría continuar días o semanas después de la finalización del embarazo (4,6). Además, en el postparto inmediato se debe descartar la presencia de complicaciones potencialmente mortales como coagulación intravascular diseminada, insuficiencia renal aguda y hemorragias gastrointestinales (18). En la lesión renal aguda se podría realizar terapia de reemplazo renal con el fin de revertir los daños y prevenir la evolución de la enfermedad (23).…”
Section: Recurrencia En Futuros Embarazosunclassified